Legalism : community and justice - Pirie, Fernanda, 1964-; Scheele, Judith, 1978- (Oxford : Oxford University Press, 2014)
That law is, or should be, related to justice generally goes without saying; that communities are the basis for (or objects of) laws is also easily assumed; and notable theories of justice explicitly or implicitly elide the two. In this volume historians and anthropologists use empirical examples to unpick conceptual knots formed by law, justice, and community, asking how these relations appear in practice, and how fundamental they are.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Justice, Administration of -- History; Justice (Philosophy); Communities -- Law and legislation; Culture and law